Ciência e religião no Rio Grande do Sul: apometria como uma prática de cura espírita - Lins, Dalvan Alberto Sabbi (2016)
This thesis is about the historical experience of a spiritualist group led by doctor Dr. José Lacerda de Azevedo who was involved with the development of a cure technique in the Hospital Espírita de Porto Alegre (HEPA) during the years of 1964 to 1986. The technique created by them, entitled apometria, characterized itself by being a system that sought to reconcile the principles of spiritism, with elements belonging to umbanda, esoterism and new age practices, all soaked and manifested through scientific lens that sought to bring aspects of parapsychology and of speculative theories, as quantum physics. Inserted in a discussion context of character of spiritism, unfolding in Rio Grande do Sul through the efforts of management that presided FERGS between the periods 1978 to 1986, the group connected to apometria ended up being the target of the internal pressures arising from a well consolidated legislative structure which had been consolidated through the work of the federal spiritualist network headed nationally by the Federação Espírita Brasileira (FEB). Thus, due to the sharply experimental and syncretistic profile of the apometria technique, it ended up being separated from the spiritistic ranks, where subsequently was proscribed and denied. The research tried historicizing this process with a view to give substance to a reflection that related to the case of apometria with other cases, approximated by the deviating and objector profile kept facing the normative structure nucleated by FEB. In this way, the case of apometria ended up showing the existence of an extensive network of social and institutional relations that remained promoting alternative spaces for discussion and exchange in the margin of the offers of the Federation. In the same way, the effort moved by this thesis, sought to think the religious phenomenon relating it to the game of interests and needs arising from the relations maintained between the individuals and institutions, in a critical work that proposes to think in a historical form the religious narratives developed and maintained by the Spiritualists groups. The search used as sources books published about the apometria technique, institutional documents of the spiritistic societies involved, regulatory, statutes, records and annals. Already to scale the discussion which was unfolding in Rio Grande do Sul about the character of spiritism, this work dates back to research in the journals of the spiritism magazine A Reencarnação, official vehicle of FERGS in editions launched between the period of 1970 to 1989.